1993
DOI: 10.1016/0014-5793(93)81715-c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of [Ca2+]i and temperature on minK channels expressed in Xenopus oocytes

Abstract: Slowly activating, voltage-dependent minK channels cloned from rat kidney were expressed in Xenopus oocytes. Increase in the bath temperature from 22 to 32°C resulted in a dramatic acceleration of minK channel activation. The extraordinarily high Q~0 of minK channel activation was voltage-dependent, being higher at more negative potentials (Q10 at -20 mV: 7.02; at 20 mV: 4.0). While activation of minK channels was highly voltage-dependent at 22°C, voltage had only little effect on minK channel activation at 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…However, previous findings for transfected COS and Chinese hamster ovary cells as well as Xenopus oocytes (4,5,15) showed that the channel regulator not only affected activation kinetics (as with our cells) but also markedly increased its density. Differences in experimental procedures may account for this discrepancy, particularly with Xenopus oocytes in which IsK-induced Kv-LQT1 current is highly temperature-dependent (16). Previous experiments were performed at 20 -22°C, whereas in our study a physiological temperature (37°C) was chosen.…”
Section: Without and With Iskmentioning
confidence: 81%
“…However, previous findings for transfected COS and Chinese hamster ovary cells as well as Xenopus oocytes (4,5,15) showed that the channel regulator not only affected activation kinetics (as with our cells) but also markedly increased its density. Differences in experimental procedures may account for this discrepancy, particularly with Xenopus oocytes in which IsK-induced Kv-LQT1 current is highly temperature-dependent (16). Previous experiments were performed at 20 -22°C, whereas in our study a physiological temperature (37°C) was chosen.…”
Section: Without and With Iskmentioning
confidence: 81%
“…I Ks in Xenopus laevis oocytes is strongly temperaturedependent [7]. Since the interaction of KCNE1 with KCNQ1 was not known at that time, the temperature dependence of KCNQ1 homomers has not been investigated so far.…”
Section: Resultsmentioning
confidence: 99%
“…This strong temperature dependence and the sigmoidal activation time course of I Ks probably reflect the complex gating mechanism of the corresponding channel complex. Since a conformational change within a preformed channel molecule is not expected to be that temperature sensitive [7] it has been proposed that KCNQ1 and KCNE1 subunits coassemble during a depolarising voltage step. This hypothesis could explain the slower activation kinetics at a lower temperature by the higher rigidity of the membrane lipids and proteins at this temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to resolve I Ks and min K single channels have been equally unsuccessful resulting instead in the recording of a macropatch current with no visible single channels in both guineapig ventricle and Xenopus oocytes Yang and Sigworth 1995). I sK and I Ks are both regulated in the same way by protein kinase A (PKA) and by calcium: I sK is enhanced by raised intracellular calcium (Busch et al 1992;Busch and Lang 1993) and activation of PKA enhanced I sK (Blumenthal and Kaczmarek 1992), increased total guinea-pig I K in the heart (Tohse et al 1987;Tohse 1990; and selectively enhanced cardiac I Ks (Sanguinetti et al 1991;Busch and Maylie 1993).…”
Section: Introductionmentioning
confidence: 99%